2019
DOI: 10.1111/psyp.13484
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and feature‐based modulation of the early posterior negativity

Abstract: The early posterior negativity (EPN) has been shown to be enhanced by emotional relative to neutral scene perception. A subset of studies has also reported a bias in the EPN toward pleasant relative to unpleasant scenes. Functional MRI research has also identified a region in lateral occipital cortex that shows a sensitivity to the visual perception of body parts, which may contribute to the EPN. Here, we assess the roles of rated scene pleasantness and the depiction of body parts on modulation of the EPN in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…For analyses of the LPP, mean amplitudes in the temporal window between 400 and 800 ms were extracted at centro-parietal electrodes CP1, CP2, P1, and P2. For both ERP components, choice of time window and electrodes was based on visual inspection of grand average waveforms, significant electrode inter-correlations and results of previous research ( Farkas et al, 2020 ; Schindler et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For analyses of the LPP, mean amplitudes in the temporal window between 400 and 800 ms were extracted at centro-parietal electrodes CP1, CP2, P1, and P2. For both ERP components, choice of time window and electrodes was based on visual inspection of grand average waveforms, significant electrode inter-correlations and results of previous research ( Farkas et al, 2020 ; Schindler et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, gender differences have been observed with reduced EPN modulation in women vs. men ( Weinberg and Hajcak, 2010 ), indicating some involvement of sex steroids. Furthermore, Farkas et al (2020) observed greater EPN negativity in reaction to erotic and nudist scenes compared to other pleasant and unpleasant visual stimuli and interpreted this as a marker of heightened attention for sexual opportunities – a process that might be modulated by OC use.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In fact, we detected no significant difference between the EPN elicited by MA-related and positive imagery, indicating that the responses were indistinguishable. The EPN is typically considered an ERP component related to early selective attentional processing and specific content distinctions of emotional stimuli (Weinberg and Hajcak, 2010;Farkas et al, 2020). Schupp et al (2006) identified the EPN as the first neural activity that reflects the emotional characteristics of a stimulus (Schupp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%